Climate change and ‘climategate’ in online reader comments: a mixed methods study - Koteyko, Nelya; Jaspal, Rusi; Nerlich, Brigitte (The Royal Geographical Society, 2013)
Climate change has rarely been out of the public spotlight in the first decade of this century. The high-profile international meetings and controversies such as ‘climategate’ have highlighted the fact that it is as much a political issue as it is a scientific one, while also drawing our attention to the role of social media in reflecting, promoting or resisting such politicisation. In this article, we propose a framework for analysing one type of social media venue that so far has received little attention from social scientists – online reader comments. Like media reporting on climate change, reader comments on this reporting contribute to the diverse, complex and contested discourses on climate change, and can reveal the meanings and discursive resources brought to the ongoing debate by laypeople rather than political elites. The proposed framework draws on research in computer- mediated communication, corpus linguistics and discourse analysis and takes into account both the content of such ‘lay talk’ and its linguistic characteristics within the specific parameters of the web-based context. Using word frequencies, qualitative study of co-text and user ratings, we analyse a large volume of comments published on the UK tabloid newspaper website at two different points in time – before and after the East Anglia controversy. The results reveal how stereotypes of science and politics are appropriated in this type of discourse, how readers’ constructions of climate science have changed after ‘climategate’, and how climate-sceptic arguments are adopted and contested in computer-mediated peer-to-peer interaction.